2002
DOI: 10.1099/0022-1317-51-11-1001
|View full text |Cite
|
Sign up to set email alerts
|

An investigation into the microflora of heroin

Abstract: In 2000, an unusual increase of morbidity and mortality among illegal injecting drug users in the UK and Ireland was reported and Clostridium novyi was identified as the likely source of the serious infection, although infections due to C. botulinum and Bacillus cereus were also reported. Because heroin was a possibile source of infection, this study investigated the microflora of heroin samples seized in England during 2000 and 2002. Two methods were developed for the examination of the microflora of heroin. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
1

Year Published

2002
2002
2017
2017

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 29 publications
0
30
1
Order By: Relevance
“…Although often considered a blood culture contaminant, B. cereus can indicate true bacteremia in the appropriate clinical context. B. cereus bacteremia has previously been reported in PWIDs ( 4 ), and cultures of heroin samples and injection drug use paraphernalia have been predominantly positive for Bacillus species ( 4 6 ). In another study, spore-forming bacteria ( B. cereus, B. anthracis, Clostridium botulinum ) were shown to contaminate heroin ( 7 ).…”
Section: The Studymentioning
confidence: 95%
“…Although often considered a blood culture contaminant, B. cereus can indicate true bacteremia in the appropriate clinical context. B. cereus bacteremia has previously been reported in PWIDs ( 4 ), and cultures of heroin samples and injection drug use paraphernalia have been predominantly positive for Bacillus species ( 4 6 ). In another study, spore-forming bacteria ( B. cereus, B. anthracis, Clostridium botulinum ) were shown to contaminate heroin ( 7 ).…”
Section: The Studymentioning
confidence: 95%
“…Tuazon et al [57] did not find S. aureus contamination of either street heroin or injection paraphernalia, and showed that most samples of street heroin had antibacterial effects against S. aureus and Bacillus cereus, possibly because of the quinine content of the drug mixture [58]. Also in a recent study, only one of 58 heroin samples examined in the United Kingdom yielded S. aureus [59].…”
Section: Contaminated Drugs and Drug-use Paraphernaliamentioning
confidence: 99%
“…However, C. novyi was not isolated from any sources associated with drug injection, including heroin seized during 2000 [15,42]. Alternatively, contamination of multiple C. novyi strains may have occurred, followed by clonal selection of a single C. novyi AFLP type which either had an adaptive advantage in spore germination, survival or growth following the drug preparation and injection procedure, or produced a more severe clinical presentation.…”
Section: B Cereus Culturesmentioning
confidence: 99%